If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -1(x + 9) = x + 4(3x + -1) Reorder the terms: 8 + -1(9 + x) = x + 4(3x + -1) 8 + (9 * -1 + x * -1) = x + 4(3x + -1) 8 + (-9 + -1x) = x + 4(3x + -1) Combine like terms: 8 + -9 = -1 -1 + -1x = x + 4(3x + -1) Reorder the terms: -1 + -1x = x + 4(-1 + 3x) -1 + -1x = x + (-1 * 4 + 3x * 4) -1 + -1x = x + (-4 + 12x) Reorder the terms: -1 + -1x = -4 + x + 12x Combine like terms: x + 12x = 13x -1 + -1x = -4 + 13x Solving -1 + -1x = -4 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -1 + -1x + -13x = -4 + 13x + -13x Combine like terms: -1x + -13x = -14x -1 + -14x = -4 + 13x + -13x Combine like terms: 13x + -13x = 0 -1 + -14x = -4 + 0 -1 + -14x = -4 Add '1' to each side of the equation. -1 + 1 + -14x = -4 + 1 Combine like terms: -1 + 1 = 0 0 + -14x = -4 + 1 -14x = -4 + 1 Combine like terms: -4 + 1 = -3 -14x = -3 Divide each side by '-14'. x = 0.2142857143 Simplifying x = 0.2142857143
| y=2x-6x+3 | | y=8x-22 | | (x-7)(x-7)=25 | | 4x-(3x+8)=6 | | 99=2(-7b-3)+7 | | 7.50+22.50x=142.50 | | 2x+8+3+4x=35 | | =9st(7s-6t^2) | | -4-73+5n=-14 | | 5+5*7=77 | | 12+11=12(x+1)+1 | | f(x)=5x-20 | | 17x+1=86 | | 2d+8=4d+8 | | x+17=267 | | 24-9=3x | | 7x=16-2(2x-3) | | x^2-220=5 | | 4y=3x+32 | | 7(a+1)-19a=-9 | | 20c-6c-6c= | | -5a-3b+8a+b= | | -4r-5r= | | 4y+3x=32 | | -3m-8=m-4 | | 5+5n=10 | | y=3x-x | | 6x-2+2x+38=180 | | -2x+5y-6x-4y= | | 9+10x=27+x | | 5x+4=5x+20 | | -10h+2=12-12h |